Safety and pharmacokinetics of the non-hormonal male contraceptive YCT-529 - Nadja Mannowetz; Stewart W. McCallum; Sharan Sidhu; Karen H. Mena; Eric P. Ruby; Ramiro Castro-Santamaria; Emily Dodds; Dennis Henderson; Gareth Whitaker; Heather Wright; Sarah Beaudoin; Akash Bakshi (Communications Medicine)
Abstract Background Since nearly half of all pregnancies in the US and worldwide are unintended, there is a critical need for additional contraceptive options for men and women. After a hiatus in non-hormonal male contraceptive development of about half a century, the new chemical entity YCT-529 – a retinoic acid receptor-α antagonist - is being developed as a non-hormonal oral male contraceptive to decrease sperm count by impairing retinoic acid signaling in the testes. Methods Here, we report the results of the first in human Phase 1a clinical trial with YCT-529 to assess its safety, tolerability, pharmacokinetics and pharmacodynamics, and its potential effects on heart rate, inflammatory biomarkers, sexual desire and mood. Sixteen male volunteers were enrolled to receive single oral doses of 10, 30, 90 or 180 mg of YCT-529 in the fasted state. Volunteers also received 30 mg in the fed state to study the effect of food on the pharmacokinetics of YCT-529. Results Single doses of up to 180 mg of YCT-529 had no effects on heart rate, hormone (follicle-stimulating hormone, luteinizing hormone, and testosterone), sex hormone-binding globulin or inflammatory biomarker levels, sexual desire or mood. Further, there was no clear food effect on the pharmacokinetics of YCT-529. Conclusions Overall, YCT-529 was well tolerated in this single ascending dose study (ClinicalTrials.gov registration: NCT06094283), which is a substantial requirement in contraceptive development.